Evaluation Of The Movement Of Cheap Food In The Context Of Controlling Inflation In The City Of Parepare - Fauzan Fuadi; Irmayani Irmayani; Muh. Ikbal Putera (International Journal of Business and Quality Research, 2025)
This study aims to evaluate the effectiveness of the Cheap Food Movement as an inflation control strategy in Parepare City initiated by the Food Security Office as an implementation of food supply and price stabilization policies in accordance with the Food Law of 2012 No. 18. By using descriptive qualitative methods through observation, interviews, and documentation, as well as triangulation techniques for data validity, the results show that GPM is carried out every Tuesday and at certain times can be done more than that is considered effective in reducing the average price of basic necessities by 15% below market prices and increasing access to quality food for people, especially low-income groups. The success of the program is strongly supported by synergy across local government agencies and the private sector, although limited food quantities are still the main obstacle. This program is considered to be able to support price stability and people's purchasing power, so the Parepare City government is encouraged to continue to increase periodic evaluations, expand the scope of distribution, and strengthen socialization so that the benefits of GPM are more optimal as an instrument to control regional inflation. This study aims to evaluate the effectiveness of the Cheap Food Movement as an inflation control strategy in Parepare City initiated by the Food Security Office as an implementation of food supply and price stabilization policies in accordance with the Food Law of 2012 No. 18. By using descriptive qualitative methods through observation, interviews, and documentation, as well as triangulation techniques for data validity, the results show that GPM is carried out every Tuesday and at certain times can be done more than that is considered effective in reducing the average price of basic necessities by 15% below market prices and increasing access to quality food for people, especially low-income groups. The success of the program is strongly supported by synergy across local government agencies and the private sector, although limited food quantities are still the main obstacle. This program is considered to be able to support price stability and people's purchasing power, so the Parepare City government is encouraged to continue to increase periodic evaluations, expand the scope of distribution, and strengthen socialization so that the benefits of GPM are more optimal as an instrument to control regional inflation.